Constitutive TNF‐α signaling in neonates is essential for the development of tissue‐resident leukocyte profiles at barrier sites. Issue 10 (29th June 2019) - Bickes, Marie Sophie; Pirr, Sabine; Heinemann, Anna Sophie; Fehlhaber, Beate; Halle, Stephan; Völlger, Lena; Willers, Maike; Richter, Manuela; Böhne, Carolin; Albrecht, Melanie; Langer, Melissa; Pfeifer, Sandra; et al.
ABSTRACT: Newborn infants have a high disposition to develop systemic inflammatory response syndromes (SIRSs) upon inflammatory or infectious challenges. Moreover, there is a considerable trafficking of hematopoietic cells to tissues already under noninflammatory conditions. These age‐specific characteristics suggest a hitherto unappreciated crucial role of the vascular endothelium during the neonatal period. Here, we demonstrate that healthy neonates showed already strong endothelial baseline activation, which was mediated by a constitutively increased production of TNF‐α. In mice, pharmacological inhibition of TNF‐α directly after birth prevented subsequent fatal SIRS but completely abrogated the recruitment of leukocytes to sites of infection. Importantly, in healthy neonates, blocking TNF‐α at birth disrupted the physiologic leukocyte trafficking, which resulted in persistently altered leukocyte profiles at barrier sites. Collectively, these data suggest that constitutive TNF‐α—mediated sterile endothelial activation in newborn infants contributes to the increased risk of developing SIRS but is needed to ensure the postnatal recruitment of leukocytes to organs and interfaces.—Bickes, M. S., Pirr, S., Heinemann, A. S., Fehlhaber, B., Halle, S., Völlger, L., Willers, M., Richter, M., Böhne, C., Albrecht, M., Langer, M., Pfeifer, S., Jonigk, D., Vieten, G., Ure, B., von Kaisenberg, C., Förster, R., von Köckritz‐Blickwede, M., Hansen, G., Viemann, D. Constitutive TNF‐α signaling in neonates is essential for the development of tissue‐resident leukocyte profiles at barrier sites. FASEB J. 33, 10633–10647 (2019). www.fasebj.org